2017
DOI: 10.1016/j.psyneuen.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate released in the preoptic area during sexual behavior controls local estrogen synthesis in male quail

Abstract: Estrogens are known to act rapidly, probably via membrane estrogen receptors, to induce fast effects on physiological and behavioral processes. Engaging in some of these behaviors, such as sexual behavior, results in an acute modulation of the production of estrogens in the brain by regulating the efficiency of the estrogen synthase enzyme, aromatase. Specifically, we recently demonstrated that aromatase activity (AA) in the male quail brain is rapidly inhibited in discrete brain regions including the medial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…The decrease in AA after engaging in sexual behavior fits with predictions made based on the rapid inhibition of AA induced by glutamate in quail HPOA explants (Balthazart et al , 2006) and the rise in extracellular glutamate concentration demonstrated in the POA of copulating male rats (Dominguez et al , 2006) and quail (de Bournonville et al , 2017). Yet, this observation seems difficult to reconcile with the rapid stimulatory role of estrogens on sexual behavior illustrated by the effects of i.c.v.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The decrease in AA after engaging in sexual behavior fits with predictions made based on the rapid inhibition of AA induced by glutamate in quail HPOA explants (Balthazart et al , 2006) and the rise in extracellular glutamate concentration demonstrated in the POA of copulating male rats (Dominguez et al , 2006) and quail (de Bournonville et al , 2017). Yet, this observation seems difficult to reconcile with the rapid stimulatory role of estrogens on sexual behavior illustrated by the effects of i.c.v.…”
Section: Discussionsupporting
confidence: 80%
“…A first group of experiments showed that the unilateral acute injection of the glutamatergic agonist kainate into the POM of anesthetized male quail inhibits after 20 minutes AA on the injected side as compared to the contralateral side that is either not injected or injected with the vehicle (de Bournonville et al , 2017). A second group of experiments then measured by in vivo dialysis variations of glutamate concentration in the POM of male quail while they were copulating with a female.…”
Section: Glutamate Modulates Aromatase Activity During Copulationmentioning
confidence: 99%
See 1 more Smart Citation
“…AA can be rapidly inhibited in vitro by calcium‐dependent phosphorylations in male and female birds . In male quail, similar effects were observed following activation of ionotropic glutamate receptors in vitro and in vivo . Although a direct link between glutamate and phosphorylation of the enzyme has not yet been demonstrated, it is likely that the glutamate‐induced depolarisation of neurones containing aromatase and the resulting changes in intracellular calcium concentration are initiating this rapid regulation of the enzymatic activity.…”
Section: Discussionmentioning
confidence: 79%
“…This effect becomes statistically significant after approximately 8 hours of exposure of castrated males to the steroid but only reaches its maximal amplitude after several days . In addition, aromatase activity (AA) is also inhibited within minutes by calcium‐dependent phosphorylations possibly mediated by the activation of glutamate receptors . These inhibitory effects of phosphorylations on AA have been confirmed not only in the hypothalamus, but also in other brain regions of another species, the zebra finch ( Taeniopygia guttata ) .…”
Section: Introductionmentioning
confidence: 94%